2021
DOI: 10.3389/fneur.2021.649014
|View full text |Cite
|
Sign up to set email alerts
|

Corticostriatal Hypermetabolism in Moyamoya Disease-Induced Hemichorea: Two Case Reports and a Literature Review

Abstract: Moyamoya disease (MMD) is a rare cause of chorea, and its pathophysiological mechanism remains unclear. We explore the use of cerebral positron emission tomography (PET) to study brain functional connectivity in 2 patients with MMD-induced hemichorea. Abnormal metabolism of brain was analyzed by 18F-fluorodeoxyglucose (18F-FDG) PET images. Dopamine transporters (DAT) PET evaluated the integrity of the cerebral dopamine system. A comprehensive systemic literature search of the PubMed database was also conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Its pathophysiological mechanism is still poorly understood; some have suggested that the choreoathetosis in MMD is a result of active ischemic changes affecting the excitatory–inhibitory circuits between the basal ganglia and the neocortex ( 6 ). A small literature review published in Frontiers in Neurology ( 16 ) revealed that hypermetabolism noticed in the pathway of basal ganglia-thalamocortical circuits using an 18F-FDG PET may explain the MMD-induced chorea, rather than the striatal hypoperfusion previously detected by SPECT ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its pathophysiological mechanism is still poorly understood; some have suggested that the choreoathetosis in MMD is a result of active ischemic changes affecting the excitatory–inhibitory circuits between the basal ganglia and the neocortex ( 6 ). A small literature review published in Frontiers in Neurology ( 16 ) revealed that hypermetabolism noticed in the pathway of basal ganglia-thalamocortical circuits using an 18F-FDG PET may explain the MMD-induced chorea, rather than the striatal hypoperfusion previously detected by SPECT ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this disease, there is reduced activation of the indirect pathway of the corticobasal ganglia—thalamocortical—loop leading to a hypermetabolic state of the striatum and cortex that eventually leads to increased activation of the excitatory neurons [ 5 ]. Cortical and subcortical hypoperfusion in frontoparietal and temporal occipital regions also may be causes of atypical manifestations of hypoperfusion [ 6 ].…”
Section: Introductionmentioning
confidence: 99%